2000
DOI: 10.1103/physrevlett.84.1184
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Hybrid Spin Resonance

Abstract: A new type of spin depolarization resonance has been observed at the Brookhaven Alternating Gradient Synchrotron (AGS). This spin resonance is identified as a strong closed-orbit sideband around the dominant intrinsic spin resonance. The strength of the resonance was proportional to the 9th harmonic component of the horizontal closed orbit and proportional to the vertical betatron oscillation amplitude. This "hybrid" spin resonance cannot be overcome by the partial snake at the AGS, but it can be corrected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The biggest impact on our determination comes from the region below 2 GeV, where the R-ratio is compiled from very many carefully measured exclusive-channel contributions. While much improved inclusive data in the region between 2 and 3 GeV have more recently become available [16][17][18], we found that, at present, these inclusive data do not have much impact on the precision of our determination. In this respect, prospects for the release of new inclusive R-ratio data by BESIII [43] and the experiments at Novosibirsk (SND, CMD-3, KEDR) are potentially promising.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The biggest impact on our determination comes from the region below 2 GeV, where the R-ratio is compiled from very many carefully measured exclusive-channel contributions. While much improved inclusive data in the region between 2 and 3 GeV have more recently become available [16][17][18], we found that, at present, these inclusive data do not have much impact on the precision of our determination. In this respect, prospects for the release of new inclusive R-ratio data by BESIII [43] and the experiments at Novosibirsk (SND, CMD-3, KEDR) are potentially promising.…”
Section: Discussionmentioning
confidence: 66%
“…These contributions to ρ EM (s) are suppressed by a factor of (m 2 s − m 2 l ) 2 /(N c s 2 ), the fourth order mass dependence arising because two mass insertions are required in each of the disconnected loops if the loop integral is to survive after the sum over all of u, d and s running around the loop is performed. 16 We observe that the first three resonances are nearly degenerate, and have approximately equal width over mass ratios (except the ω(782), for which the width is restricted by phase space).…”
Section: Duality Violationsmentioning
confidence: 78%
See 1 more Smart Citation
“…This is because Y(4260) is totally different from the predicted ψ(4S ) since the widths of Y(4260) and predicted ψ(4S ) are quite different from each other, i.e., Y(4260) is a broad state with the width 120 ± 12 MeV [30], while the predicted ψ(4S ) have a narrow width as indicated in Ref. [6], which can be the reason why the predicted ψ(4S ) is not described in the analysis of the open-charm decay channels [38][39][40][41][42] and the R value scan [43][44][45][46][47][48][49][50].…”
Section: Conlcusions and Discussionmentioning
confidence: 99%
“…as accurate measurement of the τ lepton mass [3,4], accurate measurement of the Z resonance parameters [5,6,7,7], and so forth. Thirdly, scan measurement can add a lot to understand the present theory, such as R-value measurement [8,9] and phase angle measurement [10], both of which are crucial for quantum chromodynamics researches.…”
Section: Introductionmentioning
confidence: 99%